Pneumatic rupture of the colon - Torterolo, Edgardo G; Traibel, Jorge; Devecchi, Jorge; Perrier, José P (Cirugía del Uruguay, 1977)
A 31-year-old patient was suffering from serious colonic necrosis due to high-pressure insufflation. Peritonitis and pneumo-peritonitis were diagnosed 5 hours after the patient's admission into hospital. Anatomical and ,pathogenic characteristics were those of a vascular lesion secondary to high pressure distension. These anatomical lesions have not been reported in similar cases found in literature.